Temporal trends of enterococcal and vancomycin-resistant Enterococcus faecium bacteraemia in the northern Dutch-German cross-border region: A 10-y multicentre analysis (2013–2022) - Cansu Cimen; Andreas Voss; Josef Hellkamp; Axel Hamprecht; Matthijs S. Berends (Journal of Global Antimicrobial Resistance)
Objective: To analyse the trends in occurrence of enterococcal and vancomycin-resistant Enterococcus faecium (VREfm) bacteraemia in the northern Dutch-German cross-border region. Methods: A retrospective cross-sectional study was conducted using positive blood culture results from two university hospitals, the University Medical Centre Groningen (UMCG) and the Klinikum Oldenburg (KOL) between 1 January 2013 to 31 December 2022. Results: Over the 10-y period, 738 enterococcal bacteraemia episodes were observed at KOL and 1091 at UMCG, involving 685 and 999 patients, respectively. E. faecium was the predominant species in both institutions (60.3% at KOL and 60.8% at UMCG). The median age of patients with enterococcal, E. faecium, E. faecalis and VREfm bacteraemia was consistently higher at KOL than at UMCG (p= .029). In both institutions, over half of the enterococcal bacteraemia cases (53.4% at KOL, 55.8% at UMCG) were observed in intensive care units and haematology/oncology wards. From 2018 to 2022, UMCG had higher overall incidence rates of E. faecium, and E. faecalis bacteraemia, while KOL had a significantly higher incidence of VREfm (0.56 vs. 0.05 per 10,000 patient-d, p< .0001). There was a significant upward trend in VREfm bacteraemia cases (p= .01) and in the proportion of VREfm among bacteraemia caused by E. faecium (p= .027) at KOL, but such a trend was not observed at UMCG during the study period. Conclusions: The results reveal a significant difference in VREfm bacteraemia occurrences between a German and Dutch hospital in a cross-border region, reflecting national trends yet showing regional variation.